(untitled) (Academicia Globe: Inderscience Research, 2023)
The article is devoted to a comparative analysis of crime control systems in the field of trafficking in narcotic drugs and psychotropic substances at the international level. This article discusses the problems of detecting and preventing offenses, as well as controlling the circulation of narcotic drugs and psychotropic substances in various countries of the world.